2016
DOI: 10.12669/pjms.326.10615
|View full text |Cite
|
Sign up to set email alerts
|

Use of Aspirin and Statin as primary prevention for cardiovascular diseases

Abstract: Objective:To ascertain whether recommendations for the use of Statins and Aspirin as primary prevention in diabetic patients are correctly implemented at our institution.Methods:This cross-sectional study was conducted between February 2014 and April 2014 at the General Practice Department of King Abdulaziz University Hospital. Three hundred twelve patients were included in the study. Data were collected from the electronic patient medical records for the characteristics of the patients, existing co-morbiditie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…This mechanism leads to various derangements in the lipid metabolism resulting in various dyslipidemias. 19 In our present study, 20,21 As per the general age group involved in T2DM, almost all our patients (95.4%) were 40 plus, with nearly 61% in 50-69-years of age group. In our study, for diabetic patients, the odds of having comorbidities are 7.33 and 20.14 times higher in the age group 60-69 years and 70-79 years, respectively, as the odds for age less than 40 years having comorbidities.…”
Section: Discussionsupporting
confidence: 47%
“…This mechanism leads to various derangements in the lipid metabolism resulting in various dyslipidemias. 19 In our present study, 20,21 As per the general age group involved in T2DM, almost all our patients (95.4%) were 40 plus, with nearly 61% in 50-69-years of age group. In our study, for diabetic patients, the odds of having comorbidities are 7.33 and 20.14 times higher in the age group 60-69 years and 70-79 years, respectively, as the odds for age less than 40 years having comorbidities.…”
Section: Discussionsupporting
confidence: 47%
“…It has been reported that aspirin primarily inhibits cyclooxygenase-1 irreversibly and reduces the synthesis of thromboxane A2, which prevents platelet aggregation and thrombosis. [ 16 ] Clopidogrel, ticlopidine, and cilostazol are other antiplatelet agents used to treat or prevention of cardiovascular diseases. Anticoagulant agents, such as warfarin, dabigatran, and rivaroxaban, act as vitamin K antagonists in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Similar study was done at different region of Saudi Arabia to evaluate the recommendation of aspirin as well as statin treatment in patients with diabetes to prevent CVD. This study found that aspirin was indicated and prescribed in 36.2% of the patients while in aspirin was indicated but not recommended in 17.0% of the patients ( Alkhail et al, 2016 ).…”
Section: Introductionmentioning
confidence: 94%
“…Aspirin has been approved by the U.S. food and drug administration (FDA) to be use as secondary prevention agent of cardiovascular diseases (CVD) ( Durlaza-prescribing information, 2015 ). Its advantage was significantly noticeable in decreasing CVD morbidity and mortality in patients with high risk of CVD or those underwent CVD procedures ( Bryant, et al, 2006 , Algra and Rothwell, 2012 , Williams et al, 2015 , Alkhail et al, 2016 , Abdelaziz et al, 2019 ). Several randomized clinical controlled trials have assessed the role of aspirin as primary prevention agent.…”
Section: Introductionmentioning
confidence: 99%